Surgical repair of left ventricular free-wall rupture complicating acute myocardial infarction: a single-center 30 years of experience - Matteucci, Matteo; Ferrarese, Sandro; Mantovani, Vittorio; Corazzari, Claudio; Cappabianca, Giangiuseppe; Messina, Corinne; Garis, Sara; Severgnini, Paolo; Lorusso, Roberto; Musazzi, Andrea (Frontiers in Cardiovascular Medicine, 2024)
Background. Left ventricular free-wall rupture (LVFWR) is a catastrophic complication of acute myocardial infarction (AMI). Historically, cardiac surgery is considered the treatment of choice.However, because of the rarity of this entity, little is known regarding the efficacy and safety of surgical treatment for post-infarction LVFWR. The aim of this study was to report a single-center experience in this field over a period of 30 years.Methods. Patients who developed LVFWR following AMI and underwent surgical repair at our Institution from January 1990 to December 2019 were considered. The primary end-point was inhospital morality rate; secondary outcomes were long-term survival and postoperative complications.Multivariate analysis was carried out by constructing a logistic regression model to identify risk factors for early mortality.Results. A total of 35 patients were enrolled in this study. The mean age was 68.9 years; 65.7% were male. The oozing type of LVFWR was encountered in 29 individuals, and the blowout type in 6 subjects. Sutured repair was used in 77.1% of patients, and sutureless repair in the remaining cases.The in-hospital mortality rate was 28.6%. Low cardiac output syndrome was the main cause of postoperative death. Multivariable analysis identified age > 75 years at operation, preoperative cardiac arrest, concurrent ventricular septal rupture (VSR) as independent predictors of in-hospital death. Follow-up was complete in 100% of patients who survived surgery (mean follow-up: 9.3 ± 7.8 years); among the survivors, 16 patients died during the follow-up with a 3-year and 12-year overall survival rate of 82.5% and 55.2%, respectively.Conclusions. Surgical treatment of LVFWR following AMI is possible with acceptable in-hospital mortality and excellent long-term results. Advanced age, concurrent VSR and cardiac arrest at presentation are independent risk factors of poor early outcome.